Errores al enfrentar amenazas a la Seguridad Nacional: El caso de la pandemia - Núñez del Prado, Yuri (2023)
The objective of this paper is to identify the main errors that the Peruvian State made in the management of the pandemic and that led it to be the country with the highest number of deaths per capita in the world. For this, in the pre-pandemic scenario, the differences between risk and threat will be specified, the documents that identify the pandemic as a threat to national security and as a disaster will be briefly analyzed; and the unfulfilled international commitments of the State regarding disaster risk management. Then the regulations and internal processes of national institutions responsible for the identification, planning and management of the threat will be examined, discovering in the analysis their administrative, organizational and functional shortcomings. Next, the adverse effects that arise as a result of the impact of the pandemic will be identified to determine the importance of their management. The results lead us to conclude that despite having administrative, organizational and functional institutions with sufficient elements for threat management, from the highest level, they underestimated the speed with which the probability of occurrence and the impact of the threat grew. Itself, establishing wrong criteria for threat management from government policy to operational levels, which led to it becoming a disaster of biological origin, resulting in enormous damage to the country, but mainly and particularly for thousands of Peruvian citizens who lost their lives.